2021
DOI: 10.20885/ambr.vol1.iss2.art5
|View full text |Cite
|
Sign up to set email alerts
|

The role of financial knowledge in realizing financial behavior: is it any mediating effect of financial attitudes and self-efficacy?

Abstract: The purpose of the study was to analyze the effect of financial knowledge on financial behavior with financial attitudes and self-efficacy as mediating variables. The population of this research is that all students in Semarang are unknown. The number of respondents to 96 people. The sample selection method is purposive sampling, namely: students have taken courses in financial management and intermediate financial accounting and the analytical tool used in this study was Warp PLS version 5.0. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Individual decisions based on specific emotions such as anger and anxiety will make financial decisions inappropriate. In contrast to individuals with high financial control, their behavior is more likely to have a positive attitude toward financial planning (Maulida et al, 2021).…”
Section: Financial Attitudementioning
confidence: 93%
“…Individual decisions based on specific emotions such as anger and anxiety will make financial decisions inappropriate. In contrast to individuals with high financial control, their behavior is more likely to have a positive attitude toward financial planning (Maulida et al, 2021).…”
Section: Financial Attitudementioning
confidence: 93%
“…Financial attitude specifically financial risk tolerance was found to influence one aspect of financial behaviour of gold investment (Fauzi et al, 2017). In a recent study, financial attitudes and self-efficacy were found to have a positive and significant direct effect on the financial behaviour of students in Semarang City (Maulida et al, 2021).…”
Section: Debt Attitudementioning
confidence: 94%